Toward real-time digital pulse process algorithms for CsI(Tl) detector array at external target facility in HIRFL-CSR - Liu, Tao; Song, Hai-Sheng; Yu, Yu-Hong; Yan, Duo; Sun, Zhi-Yu; Tang, Shu-Wen; Lu, Fen-Hua; Wang, Shi-Tao; Zhang, Xue-Heng; Li, Xian-Qin; Yang, Hai-Bo; Fang, Fang; et al. (Nuclear science and techniques, 2023)
A fully digital data acquisition system based on a field-programmable gate array (FPGA) was developed for a CsI(Tl) array at the external target facility (ETF) in the Heavy Ion Research Facility in Lanzhou (HIRFL). To process the CsI(Tl) signals generated by γ -rays and light-charged ions, a scheme for digital pulse processing algorithms is proposed. Every step in the algorithms was benchmarked using standard γ and α sources. The scheme, which included a moving average filter, baseline restoration, leading-edge discrimination, moving window deconvolution, and digital charge comparison, was subsequently implemented on the FPGA. A good energy resolution of 5.7% for 1.33-MeV γ -rays and excellent α - γ identification using the digital charge comparison method were achieved, which satisfies CsI(Tl) array performance requirements.